Odpowiedź :
Odpowiedź:
[tex]x=-1\frac{1}{2}=-\frac{3}{2}\\\\y=- \frac{1}{2}\\\\-x^2y+x^3y-2x^3y+x^2y+xy^3=-x^3y+xy^3 \\ \\(-\frac{3}{2})^3*(-\frac{1}{2})+(-\frac{3}{2})*(-\frac{1}{2})^3=[(-\frac{3}{2})*(-\frac{1}{2})]*[(-\frac{3}{2})^2+(-\frac{1}{2})^2]=\frac{3}{4}*(\frac{9}{4}+\frac{1}{4})=\frac{3}{4}*\frac{10}{4}=\frac{15}{8}=1\frac{7}{8}[/tex]
Szczegółowe wyjaśnienie:
x= -1 1/2= -1,5
y= - 1/2= -0,5
-x^2+ x^3 y- 2x^3y+ x^2y xy^3=x^3y+xy^3
(-1,5)^3* (-0,5)+ (-1,5)* (-0,5)^3= [(-1,5)*(-0,5)]* [(-1,5)^2+(-0,5)^2]= 1,5* 2,5=3,75
Mam nadzieje że pomogłam